Politicizing Islam in Central Asia: From the Russian Revolution to the Afghan and Syrian Jihads - Collins, Kathleen (Oxford University Press, Incorporated, 2023)
In Politicizing Islam in Central Asia, Kathleen Collins explores the causes, dynamics, and variation in Islamist movements-first within the USSR, and then in the post-Soviet states of Tajikistan, Uzbekistan, and Kyrgyzstan. Drawing upon extensive ethnographic and historical research on Islamist mobilization across numerous post-Soviet Central Asian countries, she covers over a century and explains the strategies and relative success of each movement. Collins argues that in each case, state repression of Islam and ideology motivated and enabled Islamist mobilization.